Design of innovative power conditioning system for the grid integration of thermoelectric generators - Molina, Marcelo Gustavo (2012)
Recently, thermoelectric generators (TEGs) have emerged as a potential alternative for clean energy generation, due mainly to the technology innovation and the marked cost reduction of modules, as well as their distinctive advantages. In a TEG system, the electronic power conditioning system (PCS) plays a vital role in ensuring the effective power grid integration, since it is subject to requirements related not only to the variable thermal source itself but also to its effects on the grid operation. This paper proposes an enhanced structure of PCS for the grid integration of TEG arrays to maximize the energy capture from a variable heat source. The innovative topology employed consists of a Z-source inverter that allows the flexible, efficient and reliable generation of high quality electric power from the TEG array. A full detailed model is described and its control scheme is designed. The dynamic performance of the proposed systems is fully validated by computer simulation and experimental studies.